2013
DOI: 10.1103/physrevstper.9.010113
|View full text |Cite
|
Sign up to set email alerts
|

Validating two questions in the Force Concept Inventory with subquestions

Abstract: In this study, we evaluate the structural validity of Q.16 and Q.7 in the Force Concept Inventory (FCI). We address whether respondents who answer Q.16 and Q.7 correctly actually have an understanding of the concepts of physics tested in the questions. To examine respondents' levels of understanding, we use subquestions that test them on concepts believed to be required to answer the actual FCI questions. Our sample size comprises 111 respondents; we derive false-positive ratios for prelearners and postlearner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…These values can be found in Table II. An interesting result from the presented analysis was its ability to detect potentially malfunctioning questions [38]. Questions 11,14,15,16, and 29 were all found to be potentially malfunctioning, but upon investigation only questions 16 and 29 were determined as likely malfunctioning, which is in agreement with previous research results [4,12,28].…”
Section: Limitations and Future Worksupporting
confidence: 88%
See 2 more Smart Citations
“…These values can be found in Table II. An interesting result from the presented analysis was its ability to detect potentially malfunctioning questions [38]. Questions 11,14,15,16, and 29 were all found to be potentially malfunctioning, but upon investigation only questions 16 and 29 were determined as likely malfunctioning, which is in agreement with previous research results [4,12,28].…”
Section: Limitations and Future Worksupporting
confidence: 88%
“…Because of this slight modification in the situation, option E is now awarded a partial credit score of 0.947. This question has been identified in the past as malfunctioning [4,28,29]. It has been observed that students are able to answer this question correctly through the use of Newton's first law, not through Newton's third [4].…”
Section: Question 16mentioning
confidence: 99%
See 1 more Smart Citation
“…Yasuda et al show that while question 5 scores on the FCI are marginally affected by erroneous reasoning, questions 6, 7, and 16 are more prone to guessing. These questions return a high percentage of false positives as students seem to reach the right answer while using erroneous conceptual reasoning [38,39].…”
Section: Main Concerns With Rbaimentioning
confidence: 99%
“…Since the two forces act on different bodies, this is an incorrect application of Newton's First Law that is frequently seen with students taking introductory physics. This "false positive"-obtaining the correct answer despite not correctly understanding the content tested by the question-on Q.16 was observed by the FCI creators as well as other researchers validating the FCI [3][4][5]. False positives are a source of systematic error, inflating student scores on the FCI.…”
Section: Introductionmentioning
confidence: 99%